Multicenter Comparison of 18F-FDG and 68Ga-DOTA-Peptide PET/CT for Pulmonary Carcinoid. (March 2015) - Lococo, Filippo; Perotti, Germano; Cardillo, Giuseppe; De Waure, Chiara; Filice, Angelina; Graziano, Paolo; Rossi, Giulio; Sgarbi, Giorgio; Stefanelli, Antonella; Giordano, Alessandro; Granone, Pierluigi; Rindi, Guido; et al.
<x xml:space="preserve">Abstract</x> Purpose The aims of this study were to retrospectively evaluate and compare the detection rate (DR) of 68Ga-DOTA-peptide and 18F-FDG PET/CT in the preoperative workup of patients with pulmonary carcinoid (PC) and to assess the utility of various functional indices obtained with the 2 tracers in predicting the histological characterization of PC, that is, typical versus atypical. Methods Thirty-three consecutive patients with confirmed PC referred for 18F-FDG and 68Ga-DOTA-peptide PET/CT in 2 centers between January 2009 and April 2013 were included. The semiquantitative evaluation included the SUVmax, the SUV of the tumor relative to the maximal liver uptake for 18F-FDG (SUVT/L) or the maximal spleen uptake for 68Ga-DOTA-peptides (SUVT/S), the ratio between SUVmax of 68Ga-DOTA-peptides PET/CT, and the SUVmax of 18F-FDG PET/CT (SUVmax ratio). Histology was used as reference standard. Results Definitive diagnosis consisted of 23 typical carcinoids (TCs) and 10 atypical carcinoids. 18F-FDG PET/CT was positive in 18 cases and negative in 15 (55% DR). 68Ga-DOTA-peptide PET/CT was positive in 26 cases and negative in 7 (79% DR). In the subgroup analysis, 68Ga-DOTA-peptide PET/CT was superior in detecting TC (91% DR; P < 0.001), whereas 18F-FDG PET/CT was superior in detecting atypical carcinoid (100% DR; P = 0.04). The SUVmax ratio was the most accurate semiquantitative index in identifying TC. Conclusions Overall diagnostic performance of PET/CT in detecting PC is optimal when integrating 18F-FDG and 68Ga-DOTA-peptide PET/CT findings. In the subgroup analysis, the SUVmax ratio seems to be the most accurate index in predicting TC. Both methods should be performed when PC is suspected or when the histological subtype is undefined.